Báo cáo việc lồng ghép vấn đề bình đẳng giới trong dự án Luật Bảo vệ quyền lợi người tiêu dùng (sửa đổi) - Bộ Công thương (2022)
Toàn văn Báo cáo việc lồng ghép vấn đề bình đẳng giới trong dự án Luật Bảo vệ quyền lợi người tiêu dùng (sửa đổi)